Karakterisasi sifat fisiko kimia pati bengkuang (Pachirrhyzus erosus) dan pati ganyong (Canna edulis Kerr) modifikasi [Characteristization on physico-chemical properties of modified canna (Canna edulis Kerr.) and jicama (Pachirrhyzus erosus) starches] - Sri Haryani Anwar; Yeni Chandra Dewi; Novi Safriani (Jurnal Teknologi & Industri Hasil Pertanian, 2021)
Modification of native starch is needed mainly to increase its solubility in water thus broaden its application in food industries. On the other hand, modification of canna and jicama starches have rarely been applied. Physical and chemical modifications of starches are conducted to modify starch characteristics. The research aimed to investigate the physico-chemical properties of canna and jicama starches that had been modified chemically and physically. Chemical modifications which were conducted included modification via substitution with Octenyl Succinate Anhydride (OSA) and hydrolysis using hydrochloric acid (HCl), while physical modification was conducted via the Heat Moisture Treatment (HMT). The starch physico-chemical characteristics evaluated were degree of acid (DA), swelling power, degree of substitution (DS), moisture, ash, fat, and fiber contents. The analysis results showed that moisture, ash, fat, and fiber contents of native canna and jicama starches were not significantly different from those of modified ones. The result also revealed that the type of starches and modification methods increased the swelling power significantly (P≤0,05). The DS of modified canna dan jicama starches were 0.0246% and 0.0176%, respectively. While the DA of modified canna and jicama starches were 0.14% and 0.18%, respectively. This DA values of modified starches by HCL hydrolysis had meet the Indonesian National Standard (SNI 01-2593-1992) which is maximum of 5% for food application.Keywords: canna starch, jicama starch, HMT modification, modified starch, OSA modification